ETIKA BISNIS DALAM HUBUNGANNYA DENGAN TRANSFORMASI GLOBAL DAN HUKUM KONTRAK SERTA PERBUATAN MELAWAN HUKUM - Siahaan, Hotman (Solusi, 2017)
This research uses normative juridical research method. The results of the study are: The basis of business ethics in Indonesia should be the same as business ethics around the world. Business ethics is also part of the culture of the community concerned. Therefore, the business ethics of Indonesian society must reflect the culture, civilization, values of religious character of the Indonesian nation.